Optimization of Clean Water Supply Fulfillment Strategies at Water Treatment Plants in Industrial Areas - Sonia Oktariyanti; Parwadi Moengin (Green Publisher Indonesia, 2026)
The growing demand for clean water in industrial areas requires a reliable and sustainable supply system. However, water treatment plants are operating near capacity due to tenant growth, while high energy consumption, chemical cost fluctuations, and reactive maintenance increase operational and maintenance costs. This study aims to identify optimal strategies for meeting clean water demand in industrial water treatment plant service areas by optimizing operational costs and maintaining utility networks, including operations and maintenance (O&M) improvements, small capital expenditure (CAPEX) through supply chain management (SCM) implementation, and large CAPEX such as water treatment plant expansion or new construction. The research employed financial analysis based on present value (PV) and life cycle costing (LCC) with an analysis period of 20 years and a discount rate of 8%, based on historical water treatment plant operational data and investment estimates. Scenario and sensitivity analyses were conducted to strengthen decision-making. The results show that the O&M strategy is the most optimal and highest-priority strategy, as it provides the highest cumulative cost savings without upfront investment, with PV savings on OPEX and MEX of Rp230.07–677.51 million and Rp495.26 million in the moderate scenario, respectively. The small CAPEX strategy yielded a positive net present value (NPV) saving of IDR 51.48 million but was sensitive to initial investment levels and the degree of chemical cost savings. Meanwhile, the large CAPEX strategy has a total life cycle cost of IDR 57,415.00 million and is more appropriate as a medium- to long-term solution for increasing supply capacity and reliability.